2017
DOI: 10.1039/c6lc01208f
|View full text |Cite
|
Sign up to set email alerts
|

Selection of aptamers based on a protein microarray integrated with a microfluidic chip

Abstract: We developed an efficient and fast method based on a protein microarray integrated with a microfluidic chip for the process of SELEX (systematic evolution of ligands by exponential enrichment). Lactoferrin from bovine milk was used as a target protein, while bovine serum albumin (BSA), α-lactalbumin, β-lactoglobulin and casein were used as negative proteins. They were separately dotted and immobilized to prepare the protein microarray and the resulting microarray was further integrated into a microfluidic chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…Information about them is shown in Table S1. † Especially, the sequences from YFL-1 to YFL-14 were the same as the sequences in PMM-SELEX, 33 which showed the reliability of Microarray-SELEX.…”
Section: Microarray-selex For Aptamer Selection Against Lactoferrinmentioning
confidence: 71%
See 2 more Smart Citations
“…Information about them is shown in Table S1. † Especially, the sequences from YFL-1 to YFL-14 were the same as the sequences in PMM-SELEX, 33 which showed the reliability of Microarray-SELEX.…”
Section: Microarray-selex For Aptamer Selection Against Lactoferrinmentioning
confidence: 71%
“…SA-MPs and NaOH were used to turn PCR products to ssDNA according to our previous reports. 33 Only the sixth-round PCR product of the rst cycle selection was cloned by Sangon Bio-Technology.…”
Section: Selecting Process By Microarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we describe a selection approach that builds off previous SELEX advancements, as well as incorporates a consolidated counterselection strategy, thereby generating high‐affinity and moderate specificity aptamers . We recently reported the design of a custom‐built multichannel peristaltic pump that could be used for this purpose, continuing on the theme of bringing novel ideas and low‐cost resources to the aptamer community .…”
Section: Discussionmentioning
confidence: 99%
“…Additional efficient modalities for aptamer selection include capillary electrophoresis [37][38][39] and magnetic sorting 40 . Electrophoresis and magnetic beads have been combined with microfluidics to create integrated systems for aptamer selection [41][42][43] . All these methods have demonstrated that aptamer selection could be significantly sped up and multiplexed.…”
Section: Discussionmentioning
confidence: 99%